Protagonism and autonomy in classroom: the creation of videos in english language classes in higher education - Gualda, Linda Catarina (Revista Hipótese, 2022)
The conscious use of new technologies makes it possible to use the language in authentic, meaningful contexts, fostering the learner's autonomy and protagonism. Thus, the objective is to show the students' videos, the resources used, the importance of interactivity, the moments of overcoming and learning from the experience. The study was developed with students from the first and second cycles of the Foreign Trade Course of Fatec Itapetininga/SP from 2013 to the present. Reflection on activity was generated as an integrating tool, facilitator of teaching and cultural production that promotes teamwork, communicability, imagination and sensitivity.
Keywords: Meaningful Learning; New technologies; Foreign language; Higher Technological Education